2017
DOI: 10.1016/j.biomaterials.2016.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Guided growth of auditory neurons: Bioactive particles towards gapless neural – electrode interface

Abstract: Cochlear implant (CI) is a successful device to restore hearing. Despite continuous development, frequency discrimination is poor in CI users due to an anatomical gap between the auditory neurons and CI electrode causing current spread and unspecific neural stimulation. One strategy to close this anatomical gap is guiding the growth of neuron dendrites closer to CI electrodes through targeted slow release of neurotrophins. Biodegradable calcium phosphate hollow nanospheres (CPHSs) were produced and their capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…When a cochlear implant is placed anyway, the incorporation of a delivery system seems very appropriate. Released BDNF can then act as a neuroprotective factor and might guide neurite outgrowth towards the cochlear electrode [ 37 , 45 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…When a cochlear implant is placed anyway, the incorporation of a delivery system seems very appropriate. Released BDNF can then act as a neuroprotective factor and might guide neurite outgrowth towards the cochlear electrode [ 37 , 45 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…For this to occur, neurite regeneration must first be stimulated. Several groups have demonstrated that neurotrophic factors, such as BDNF and NT-3, are sufficient to induce SGN neurite regeneration in vivo following deafening (Budenz et al, 2015; H. Li et al, 2017; Shibata et al, 2010; Wise et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al, 2017; Shibata et al, 2010; Wise et al 2005). Further, gradients of neurotrophic factors have been shown to guide SGN neurite growth in vitro (H. Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in a reference-subtracted real-time binding curve that provides information about the affinity, kinetics, and possibly also the binding mechanisms of the interaction between the ligand and the cells within the target area. The LigandTracer instrument series have previously been used in an increasing number of studies (> 70 papers as of August 2017), primarily with protein ligands and living mammalian cells expressing target receptors, but alternative ligands and targets are possible, such as small molecular drugs, nanoparticles, and antigens on magnetic beads (Björkelund et al 2011 ; Pa̧zik et al 2011 ; Mihaylova et al 2014 ; Li et al 2017 ; Zeilinger et al 2017 ; Bugaytsova et al 2017 ). A major requirement for the use of the LigandTracer instrument is the necessity to immobilize cells or the isolated receptor on the surface of a regular Petri dish.…”
Section: Introductionmentioning
confidence: 99%